A Critical Review on the Book Political Thought in Ancient Iran - Hamid Hamid Kavyani Pooya (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Researchers consider political thought as a reflection of political phenomena, which, of course, has come into being in a civilized and political society with a government structure. Each political society, based on the distinct structure that exists in the understanding and culture of its inhabitants, is distinct from other societies and has a particular attitude and mindset. Therefore, understanding the nature of the historical society and people’s behaviors and practices, as well as the causes of certain events, is possible only by studying the thought and political culture of those societies. Thus, the research can clarify the dark angles of a historical period and contribute to the richness of the audience's historical understanding. Also, the impartial and scientific critique of these works contributes to the scientific and educational richness and adds to their efficiency, usefulness, and privileges. Accordingly, in this article, one of the newly published works on Political Thought in Ancient Iran was covered to study the importance and credibility and, of course, some of its shortcomings and defects in the form and content. There is a hope of better presentation in the subsequent printing.